Influence of fat level and calorie:protein ratio on the performance of young pigs - G L Allee; Robert H Hines (Kansas Agricultural Experiment Station Research Reports, 1971)
One hundred twenty-eight pigs averaging 44 pounds were used to determine the influence of level of dietary fat and calorie:protein ratio on the performance of young pigs. Daily gains by pigs fed diets containing 0, 3, 6, 9, or 12% added fat did not differ significantly. Feed efficiency and kcal metabolizable energy per pound of gain were improved as the fat level of the diet increased. When fat was added to the diet without adjusting the calorie: protein ratio, average daily gain and energy efficiency were significantly reduced. Thus, suggesting the importance of the. calorie:protein ratio in the nutrition of young pigs. Current prices make fat an economical source of energy for young pigs.; Swine Day, Manhattan, KS, October 7, 1971
Keywords: Swine day; 1971; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 181; Swine; Fat; Calorie:Protein ratio; Performance; Young pigs